Dynamics of the Deviant Subculture Klitih Gang and Al-Fatah Transgender Boarding School in Yogyakarta - Harahap, Chisa Belinda; Triyoga, Anwar Ibrahim; Titisia, Denti (GoResearch - Research & Publishing House, 2023)
Klitih gangs in Yogyakarta, as a tangible form of juvenile delinquency, cannot be separated from the construction of the failure of environmental socialization and socialization of adolescent life in modern times. This study used interpretive approach (qualitative). Researcher digs deeper into how cultural criminology views the deviant subculture of youth members of the Klitih Gang and the dynamics of the Al-Fatah Transgender Islamic Boarding School as accurate facts. This article focuses on discussing several aspects that are interconnected with the school of cultural criminology, including (1) cases of youth violence and street crime by gangs of Klitih as a form of crime as culture; (2) community construction related to culture as crime against transgender groups, especially in the Al-Fatah transgender Islamic boarding school, Yogyakarta; (3) discussion on the realm of existentialist criminology in its allusion to ways of life, style, and semiotics. This phenomenon creates anomie in the dynamics of social life and requires efforts to harmonize both from a juridical and sociological perspective.